MRI Evaluation of Painful Hip Joint - Sahil Chhabra; Navkiran Kaur; Simmi Bhatnagar; Prerna Chhabra; Shivani Puri (Asian Journal of Medical Radiological Research, 2020)
Background: The hip is a stable, major weight-bearing joint with significant mobility. It can be involved by numerous pathological conditions like congenital and developmental, infective, arthritic, and neoplastic. Hence, early diagnosis and characterization of pathology play a vital role for the clinicians in proper management and follow-up of the disease. This study aimed to evaluate the role of MRI in the diagnosis of painful hip pathology. Subjects and Methods: This study was a prospective study; total 50 patients were included in this study. This study was conducted at the Department of Radio-Diagnosis, Rajindra Hospital, Patiala. MR Imaging was done with a 1.5 Tesla superconductive scanner (Siemens 1.5 T Magnetom AERA MRI Machine). Results: 26 out of 69 total hip joints affected (including bilateral) were diagnosed as avascular necrosis, 14 hips as osteoarthritis, and 10 hips as septic arthritis. Inflammatory arthritis was diagnosed in 7 hips, femoroacetabular impingement and an acetabular labral tear in 2 hips each. 2 cases were reported as normal hip joint and 1 case each was reported as a primary and metastatic tumor. Conclusion: MRI is the method of choice in characterizing the various disorders of the hip joint, and it can point out specific features leading to an accurate diagnosis of the painful hip joint.